Marketing communications - Eagle, Lynne (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Marketing communication is a dynamic industry, which continues to change and adapt to new technologies, media consumption patterns and communication interfaces between marketers and their target markets. At the same time, the fundamental communication processes and well-established theories and models are very much applicable in this dynamic environment. This revised second edition blends the well-established with the new and emerging aspects of marketing communications. Marketing Communications applies a uniquely practical approach to the topic, providing a structured overview of planning, development, implementation and evaluation of marketing communications, alongside detailed case studies that demonstrate how the theory translates to practice. Fully updated, the new edition considers important developments in the global marketplace. It includes new content on emerging digital media platforms, changing media consumption patterns and consumers' strategies to cope with information overload. It also reflects upon consumer skepticism, a growing phenomenon that communication specialists need to overcome when designing and implementing effective campaigns. This new edition also considers the importance of marketing communications tools in not-for-profit sectors, such as social marketing and political marketing, as well as the cross-cultural aspect of marketing communications. This textbook is essential reading for both students and professionals in marketing, communications and public relations. Online resources include an extensive instructors' guide, which provides answer checklists to all Thinkboxes, Ethical Issues and End-of-chapter Cases within the book. The text is also supported by PowerPoint slides and test bank for all chapters and major cases"--
OCLC-licensed vendor bibliographic record.
Keywords: Communication in marketing; Advertising; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Business Communication / General; BUSINESS & ECONOMICS / Marketing / General